Probiotic potential of Lactobacillus delbrueckii strains and their phage resistant mutants - Guglielmotti, Daniela Marta (2007)
Three commercial phage sensitive strains of Lactobacillus delbrueckii and spontaneous phage resistant mutants isolated from them were studied by focusing on their biological and probiotic features. After incubation in a simulated gastric solution (pH 2.0), viable cell counts decreased moderately, but a protective effect on strains was observed when milk was added. A limited resistance to bile was observed, while most of the strains tolerated lysozyme, and grew in the presence of bile salts and fermented prebiotics. Some strains showed high hydrophobicity values and β-galactosidase activity. The strong antibacterial activity displayed toward pathogens was due to the production of lactic acid. Sensitive strains and their phage resistant variants were able to adhere to Caco-2/TC-7 monolayers and significantly inhibited the invasion of Salmonella enterica serovar Enteritidis into Caco-2/TC-7 cells. All strains tested showed potential probiotic features, suggesting a potential probiotic role of L. delbrueckii.